Companies’ behavior in measuring the quality of financial reports: Pre- and post-pandemic research - Dănescu, Tatiana; Stejerean, Roxana Maria (Frontiers in Psychology, 2022)
Since information is the foundation for decision-making by its users, it and the quality associated with it must be given particular importance in order to reduce uncertainties about how it is reported and interpreted and to increase its usefulness. Financial reporting is of relatively great significance to both those who provide it and those who use it, with accounting providing a wide range of sources of financial information, ensuring a high degree of credibility compared to other sources of information. The objective of the research is to highlight the behavior of companies in measuring the quality of issuers' financial reporting to identify solutions for harmonizing the way financial information is presented with the needs of users. Two hypotheses were defined and tested for this purpose, with the research being segmented over three successive stages. The first stage consists in identifying the appropriate index to measure the quality of financial reporting. The second stage consists in gathering the data and obtaining the quality measurements, for testing the defined hypotheses. The third stage concerns in concluding the results obtained highlight the existing divergences between the period before the health crisis, but also the period immediately after the Covid-19, on the two markets of the Bucharest Stock Exchange (regulated market and AeRO market).